Słownik śląsko-chiński dla tłumaczy bez przygotowania - Karolina Pawlik (Postscriptum Polonistyczne)
The author of the article writes about an unconventional reading of a small, amateurish SilesianChinese Dictionary by Marek Jachymski. By analysing the vocabulary, structure and the reliability of the translations the author of the article is lead to asking some important questions concerning prioritization and the political aspects of languages, mechanisms of word selection, the image of language, the world expressed by the selection of vocabulary and the specific character of a dictionary as a tool used in the process of translation and intercultural communication. The author pays close attention to the linguistic and cultural adequacy of some chosen word pairs. She highlights the need to consider such matters as schematic thinking about languages, the translating of cultures and the translator’s neutrality. By suggesting some excercises, the author also shows how this dictionary can be used in didactics that aim at developing students’ cultural and linguistic awareness, in terms of language and translation.